Eksistensi Kawasan Pecinan dalam Bentuk Pemenuhan Tata Ruang Kota Jember, 1930-1970 - Jergian Jodi; Badrun Badrun (Local History & Heritage, 2022)
The formation of the district of Jember was influenced by Europeans who were interested in establishing a plantation in Jember. Jember which was originally part of the Bondowoso afdeeling then on January 9, 1883 the Governor of the Dutch East Indies made a change to a separate afdeeling and in 1928 the Dutch East Indies government issued a regulation to increase the status to Regentschap Djember as a district. Changes in status caused a large number of migrants to come, especially ethnic Chinese who made their place of residence namely the Chinatown village. The Chinatown area which is located in the city center is not only their place of residence, but their economic activities are also carried out in the area. The objectives to be achieved in this article are: (1) to determine the process of the formation of the Chinatown area in Jember Regency, (2) to determine the influence of the Chinatown area on the spatial planning of the city of Jember, 1930-1970. The method used in this study is a historical research method that contains four points, including: heuristics (data collection), verification (source criticism), interpretation, and historiography.